Biomass production and essential oil content and composition in basil hydroponic systems using treated domestic effluents - Alves, Lucylia Suzart; Gheyi, Hans Raj; Silva, Mairton Gomes da; Paz, Vital Pedro da Silva (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2021)
Reusing domestic wastewater is an alternative for irrigated agriculture, helping to decrease pressure on good quality water. This study aimed to evaluate the biomass production and essential oil content and composition in the basil genotypes ‘Alfavaca Basilicão’ and ‘Grecco a Palla’ with different plant spacing in hydroponic systems. Two experiments were carried out between March and May (Experiment I) and July and September of 2015 (Experiment II) in a completely randomized design with four replicates in a 2×3 factorial arrangement. In Experiment I, two hydroponic systems (Laminar Nutrient Flow Technique - NFT and Deep Nutrient Flow Technique - DFT) and three plant spacings in hydroponic channels (0.20, 0.30, and 0.40 m) were evaluated. In Experiment II in the DFT hydroponic system, two types of water (tap water and treated domestic effluents) and three nutrient solution recirculation intervals (at intervals of 2, 4, and 6 h) were evaluated. In general, the dry biomass per plant, oil content and oil yield of the two basil genotypes were not influenced by the hydroponic systems, plant spacing, or water type. In Experiment II, the increase between the recirculation intervals (4 or 6 h) negatively affected genotype ‘Grecco a Palla’. Linalool was the major constituent in the essential oil of the two basil genotypes, ranging from 47.00 to 70.10% (Experiment I) and from 59.47 to 63.64% (Experiment II) in genotype ‘Alfavaca Basilicão’; in genotype ‘Grecco a Palla’, it ranged from 10.19 to 43.03% (Experiment I) and from 19.94 to 53.37% (Experiment II).